EVALUATION OF KNOWLEDGE, ATTITUDE, AND PRACTICE ABOUT PHARMACOVIGILANCE AMONG NURSING STAFF AT TERTIARY CARE TEACHING HOSPITAL - RUSHITABEN K BHUNGALIYA; GOSWAMI, NIMIT; SHAH, SHREYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The primary objective of this study was to evaluate the knowledge, attitude, and practice of nursing staff about pharmacovigilance and adverse drug reactions (ADRs) reporting in a tertiary care teaching hospital. The secondary objective was to assess the causes of underreporting of ADRs. Methods: A cross-sectional questionnaire-based study was carried out using a pre-designed structured questionnaire, adapted from previous studies and validated internally among the members of the pharmacovigilance committee. This questionnaire was provided to the nurses of all wards and out-patient department in a tertiary care teaching hospital of Gujarat, after taking their written informed consent. The data were evaluated for further analysis. Results: Out of 309 participants, 73.38% had appropriate knowledge about pharmacovigilance and ADRs and 72.41% had a positive attitude toward the safety of drugs and reporting of ADRs. Out of 309 nurses, 55.34% of nurses came across an ADR and 3.56% of nurses had reported an ADR. According to the evaluated data, the reasons for underreporting of ADRs were lack of awareness, lack of time, and fear of legal implications. Out of all participants, 4.85% had attended ADR training/awareness sessions. Conclusion: In the present study, nursing staff at a tertiary care teaching hospital had good knowledge and positive attitude toward pharmacovigilance but at the same time application of the same was lacking. Exposure to awareness programs and seminars about pharmacovigilance and hands-on ADR training sessions can improve the practice of nurses about pharmacovigilance.